Analysis of the Suitability of Teachers' Way of Teaching Passing Techniques in Volleyball - Djanji Djalminha Iftisary; Rudi Rudi; Indraypgi Indrayogi (Universitas Majalengka, 2023)
Volleyball is a complex game that is not easy for everyone to play. The techniques in volleyball games taught by teachers in several schools are still lacking in conformity with the proper underhand passing technique rules. The purpose of this research is to analyse the suitability of physical education teachers for teaching the bottom passing technique. It aims to improve the ability of underhand passing in volleyball games for students. The method used in this research is qualitative. Qualitative research is a method that contains descriptive data and tends to use analysis. The data obtained from this study were SDN Ciborelang II (50%), SDN Ciborelang III (85%), and SDN Leweung Gede IV (60%). The suitability of the teacher's way of teaching the bottom passing technique at three public elementary schools in Jatiwangi District, Majalengka Regency, is 85%–100%, which is in accordance with the existing indicators.